Dual control of multi-band resonances with a metal–halide perovskite-integrated terahertz metasurface. Issue 35 (22nd August 2022) - Lu, Yuying; Li, Tengteng; Yang, Maosheng; Yao, Haiyun; Liang, Lanju; Yan, Xin; Lv, Kai Kai; Wang, Meng; Yang, Qili; Wei, Chaoyang; Shao, Jianda; Yao, Jianquan
Abstract : Here, we report dual control of multi-band Fano resonances with a metal-halide perovskite-integrated terahertz metasurface by lasers and electrical fields through tuning the conductivities of the perovskite film with the highest depth of 197%. Abstract : The phenomenon of multi-resonant Fano resonances is important for the design of biosensors and communication fields. There are very few studies reporting the multi-band Fano resonance metamaterials with more than three resonance frequencies, or the tunable optical metamaterials to control the multi-band Fano resonance characteristics. Here, we report dual control of multi-band Fano resonances with a metal–halide perovskite-integrated terahertz metasurface by lasers and an electrical field. By tuning the conductivity of the perovskite film on the metasurface, ultrasensitive optoelectronic modulation was achieved. The terahertz transmission amplitude exhibited increasing and decreasing stages. We analyzed the physical phenomena and found that capacitance effects and Fermi-level enhancement had significant roles in the optical- and electronic-modulation experiments. The resonant frequencies in the electronic modulation had broader frequency shifts and a higher and wider tunable modulation depth range. More importantly, the maximum modulation depth was as high as 197%, with a significant fluctuation in the amplitude and more unstable frequency shifts in the transmission spectra.